Advanced Electrochemical in Vitro Detection of Superoxide Radicals with Fully Integrated Microsensor System. (2015) - Flamm, H.; Kieninger, J.; Weltin, A.; Urban, G.A.
Abstract: An electrochemical sensing system for in vitro measurement of superoxide radical is presented. The approach of the system is based on a fully integrated sensor setup in conventional tissue culture containment, utilizing novel direct oxidation of ROS on polymer covered gold microelectrode. The concept was shown to provide stable and sensitive measurement procedure without the need for enzymatic recognition elements. Sensor performance was investigated from artificial enzymatic superoxide production, with a sensitivity of 2247 AM -1 m 2 and outstanding high selectivity for main interfering substances. Online monitoring of superoxide release from human breast carcinoma cell line T-47D was successfully demonstrated.